Nature-Based Solutions (Nbs) In The Implementation Of Flood Policies: Inconsistencies And Impacts In Jakarta - Adha, Alifia Nadhira; Salomo, Roy Valiant (UNIVERSITAS PAKUAN, 2024)
The global trend of NbS is a new thing as a reference for government initiatives in determining the flood policies in Jakarta. However, NbS through the concept of river naturalization is considered as a causing of inconsistency in the implementation of flood policies. This research aims to analyze the phenomenon of flood policy inconsistency along with the impacts and obstacles in the implementation of NbS. This research uses a qualitative method by conducting in-depth interviews and document studies. The results of this study conclude that the implementation of NbS in Jakarta has not been optimal with various underlying factors behind it. These factors include the lack of collaboration among the actors involved; the lack of suitability of the topographical conditions of the area; and the lack of suitability of the community and natural ecosystems.